Characterization of consultations for odontogenic abscesses in a major Chilean hospital - Santander, Maite; Maggi, Tatiana (Journal of Oral Research, 2019)
To characterize consultations for odontogenic abscesses at the Dental and Maxillofacial Unit of the Public Emergency Hospital in Santiago, Chile. Methodology: Descriptive study, involving consecutive sampling of patients with diagnosis of odontogenic abscess, conducted between August and September 2016. Descriptive statistics were performed to determine the frequency of diagnosis, affected tooth, sex and need for hospitalization. Results: Odontogenic abscesses accounted for 6.3% (n=414) of a total of 6,535 consultations. Males represented 59%; 42% of odontogenic abscesses presented in molars and maxillary premolars. The vestibular space was the most frequently affected anatomical space (50%), associated in 53% of the cases to submucosal abscesses. Ninety-eight per cent of patients were successfully treated on an outpatient basis, 2% required hospitalization, mainly associated to abscesses involving the deep submandibular space. Conclusion: Odontogenic abscesses account for a low percentage of dental emergencies at the Public Emergency Hospital in Santiago, Chile. Most cases receive outpatient treatment.